Comparison and classification of six reference currents extraction algorithms for harmonic compensation on a stochastic power network: Case of the TLC hybrid filter. Issue 1 (31st December 2022) - Assiene Mouodo, Luc Vivien; Mahamat ALI, Abdel-Hamid; Tamba, Jean Gaston; Olivier, Thierry Sosso Mayi
Abstract: This article highlights a comparison and classification of six algorithms for extracting reference currents used in the context of harmonic compensation for the case of a TLC hybrid filter on a stochastic electrical network. With the ultimate goal of determining the most robust and reliable algorithm, the electrical network presents four variable configurations such as, operation in sinusoidal and balanced voltage, sinusoidal and unbalanced voltage, balanced and disturbed voltage, or even in unbalanced voltage and disrupts. Firstly, a presentation of these six algorithms or methods identified in the time domain will be made with injections of the fifth-order harmonics taken in positive sequences during the execution or compilation of the six algorithms for the four network operating hypotheses. And in a second step, a cross-comparison of the performances on the basis of indicators such as the THD (harmonic distortion rate) and UFI (unbalance factors) required by the IEEE 519–2014 and EN 50160 standard, then a cross-validation is based on some results available in the literature. These results will now facilitate the choice of the most appropriate algorithm depending on the nature of the electrical network in force according to the case studies.